Amyloid-β25–35 peptides aggregate into cross-β sheets in unsaturated anionic lipid membranes at high peptide concentrations. Issue 13 (26th February 2016) - Tang, Jennifer; Alsop, Richard J.; Backholm, Matilda; Dies, Hannah; Shi, An-Chang; Rheinstädter, Maikel C.
Abstract : A membrane mediated interaction leads to the formation of peptide clusters inside the bilayers, which may serve as nuclei for further growth into amyloid fibrils. Abstract : One of the hallmarks of Alzheimer's disease is the formation of protein plaques in the brain, which mainly consist of amyloid-β peptides of different lengths. While the role of these plaques in the pathology of the disease is not clear, the mechanism behind peptide aggregation is a topic of intense research and discussion. Because of their simplicity, synthetic membranes are promising model systems to identify the elementary processes involved. We prepared unsaturated zwitterionic/anionic lipid membranes made of 1-palmitoyl-2-oleoyl- sn-glycero -phosphocholine (POPC) and 1, 2-dimyristoyl- sn-glycero -3-phospho-l -serine (DMPS) at concentrations of POPC/3 mol% DMPS containing 0 mol%, 3 mol%, 10 mol%, and 20 mol% amyloid-β25–35 peptides. Membrane-embedded peptide clusters were observed at peptide concentrations of 10 and 20 mol% with a typical cluster size of ∼11 μm. Cluster density increased with peptide concentration from 59 (±3) clusters per mm 2 to 920 (±64) clusters per mm 2, respectively. While monomeric peptides take an α-helical state when embedded in lipid bilayers at low peptide concentrations, the peptides in peptide clusters were found to form cross-β sheets and showed the characteristic pattern in X-ray experiments. The presence of the peptides was accompanied by an elastic distortion of the bilayers, which can induce a long range interaction between the peptides. The experimentally observed cluster patterns agree well with Monte Carlo simulations of long-range interacting peptides. This interaction may be the fundamental process behind cross-β sheet formation in membranes and these sheets may serve as seeds for further growth into amyloid fibrils.